PENGARUH IMMEDIATE FEEDBACK TERHADAP KEPERCAYAAN DIRI DAN PEMAHAMAN KONSEP SISWA PADA MATERI STOIKIOMETRI SMA - Mulida, Mulida; Sartika, Rody Putra; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to determine whether there was a difference in self-confidence and understanding of the concept of tenth grade students of SMA Negeri 1 Tekarang who were given immediate feedback and the student who were given conventional methods on stoichiometric material, and also to know how much immediate feedback influences the conceptual understanding of tenth grade students at SMA Negeri 1 Tekarang on stoichiometry material. The research method used was quasy-experiment, with Nonequivalent Control Group Design. The sampling used was saturated sampling techniques with class X MIA 2 as experimental class students and class X MIA 1 as control class students. Self-confidence questionnaire, understanding concept test, observation sheet and interview guidelines were used to collect data. The results analysis of final questionnaire and posttest data using SPSS 17 for windows with the Mann Whitney U-test obtained Asymp.Sig (2-tailed) values of 0.004 and 0.000 respectively, this indicated that there was a difference self-confidence and understanding of concepts of the students who were given immediate feedback and the student who were given conventional methods on stoichiometric material. The amount of influence given by immediate feedback on students conceptual understanding was 70.7% with a high category. Keywords: Immediate Feedback, Self-Confidence, Conceptual Understanding, Stoichiometry.